The deserter [compact disc, unabridged] : a novel - DeMille, Nelson; DeMille, Alex (Audioworks, Simon & Schuster Audio, 2019)
A year after a trained assassin with classified Army intelligence disappears under suspicious circumstances, the efforts of Army investigator Scott Brodie to capture the man alive are complicated by his partner's inexperience and suspected role as a CIA spy.